Ouran High School Host Club. Vol. 05 - Hatori, Bisco (Shojo beat manga., 2005)
Haruhi is in danger of losing her scholarship as her ranking falls. The members of the Host Club each offer to tutor her but she chooses a female student who doesn't like Tamaki. Now Tamaki has to figure out a way into her good graces so the Host Club can continue spending time with Haruhi.